Traumatic brain injury manifested as optic neuropathy in the horse: A commentary and clinical case. (9th July 2014) - Brooks, D. E.; Plummer, C. E.; Craft, S. L. M.; Struthers, J. D.
Summary Blindness from head trauma is a serious debilitating disease in the horse. It appears that blunt trauma to the skull results in intracranial injury to the optic nerve at the optic chiasm from mechanical and vascular mechanisms. Systemically administered iron and calcium chelation therapy may enable some horses to recover vision.